What can we learn from Malay vernacular houses? - Ghaffarian Hoseini, Amir Hosein; Berardi, Umberto; Dahlan, Nur Dalilah; Ghaffarian Hoseini, Ali (Elsevier BV, 2014)
Today, the contemporary residential design has been promoted in cities without concerns of the essence of vernacular houses. Recent studies declare that the quality of contemporary residential spaces is often poorly linked to traditions and value of each region. In view of the rapid modernization of Malaysia, the kampong houses as Malay vernacular built environments have been replaced by modern residential design. Thus, several aspects of kampong which embody major vernacular values are lost. Accordingly, many Malay inhabitants still prefer to live in houses that are based on their own traditions. This is because quality of housing as one of the fundamental factors in enhancing the quality of life is not fully in line with their daily lifestyle and local environmental characteristics. Hence, the congruency among local daily functions, environmental characteristics of region, and vernacular functional spatial features is perceived as a substantial principle for enhancing the quality of life. The study theorizes that the aforementioned congruity must be considered during the contemporary residential design in order to address the actual needs of users for enhancing their quality of life. In this line, theoretical analysis concludes that among all identified values, privacy and optimal use of space are the significant social values while natural ventilation is the most significant environmental value extracted from the analysis of Malay houses.